HISTOPATHOLOGICAL STUDIES ON THE LIVER AND GILLS IN CARASSWS AVRATUS EXPOSED TO COPPER SULPHATE - Sultan, Salim; Khan, S Mahmood (Indian Journal of Fisheries, 2011)
Acute and chronic exposure to copper sulphate results in destruction of cytoplasmic material and vacuolation of hepatocytes in Carassius auratus. The blood sinusoids also undergo degeneration. Light microscopic studies show severe histopathological changes in gills due to exposure. Fishes exposed to chronic concentration are more prone to disintegration